DAMPAK KAWIN PAKSA TERHADAP KEHAMONISAN RUMAH TANGGA DALAM PERSPEKTIF HUKUM ISLAM (Analisis Desa Panaan Kecamatan Palengaan Kabupaten Pamekasan) - Hafas, Imam (Mitsaqan Ghalizan, 2021)
Normal family life in marriage is the rights and needs of every human being. Therefore, it is natural that before entering domestic life both men and women use a lot of considerations in choosing and determining a partner. Not a few cases were found in the community regarding a married life that was motivated by compulsion to hold a marriage, which was then known as forced marriage. As for the study of the problems that become the main study in this discussion, they are about the occurrence of forced marriages, the view of Islamic law on forced marriages, and the impact of forced marriages in household harmony. The method in this study uses juridical and normative analysis methods or field research, in which data collection techniques use primary data and secondary data.